2022
DOI: 10.1037/gdn0000129
|View full text |Cite
|
Sign up to set email alerts
|

Independent self-concept promotes group creativity in a collectivistic cultural context only when the group norm supports collectivism.

Abstract: How does independence in self-concept affect group creativity in a collectivistic cultural context? Unlike the Western perspective that emphasizes individualism as the impetus to group creativity, we propose that in a cultural environment where collectivistic values are predominant, a combination of group members' independent self-concept and a collectivistic group norm promotes group creativity. In an experiment involving three-person laboratory groups (N = 64 triads), we primed group members with an independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Specifically, originality-focused instruction enhanced individual creativity for American students, while appropriateness-focused instruction promoted team creativity for Chinese students. As discussed in previous studies (Choi et al, 2019;Lee & Choi, 2022), the group interaction level can magnify the role of cultural norms, which in turn makes the cultural difference more robust. We suspect that the team work modality could activate their collectivistic cultural norms, which further improved team creativity.…”
Section: Theoretical Implicationsmentioning
confidence: 82%
See 2 more Smart Citations
“…Specifically, originality-focused instruction enhanced individual creativity for American students, while appropriateness-focused instruction promoted team creativity for Chinese students. As discussed in previous studies (Choi et al, 2019;Lee & Choi, 2022), the group interaction level can magnify the role of cultural norms, which in turn makes the cultural difference more robust. We suspect that the team work modality could activate their collectivistic cultural norms, which further improved team creativity.…”
Section: Theoretical Implicationsmentioning
confidence: 82%
“…Although our power analyses indicated that a sample size of 48 teams with 144 individuals was sufficient to test the proposed effects, a large sample-particularly a large number of teams-may be desired for future study. We also noticed that although previous studies (Choi et al, 2019;Lee & Choi, 2022) investigated the mechanism of the cultural norm on creativity by manipulating the cultural norms (i.e., via activation of the cultural identity of individuals), we did not adopt the same method examining the cultural norm. As aforementioned, it was unclear which one -the instructional focus or work modality-activated the cultural norms and influenced creative performance.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed the authors to assess differences among groups and verify the connection between culture and creativity (Ge et al, 2021;Haines, 2013;Koronis et al, 2019;Liou & Lan, 2018;Nouri et al, 2015;Peng et al, 2021;Saad et al, 2015;Wodehouse et al, 2011;Wodehouse & Maclachlan, 2014;Yi et al, 2013;Zheng et al, 2022). Seven studies conducted in a single country recruited participants and manipulated their cultural values before ideation (Bechtoldt et al, 2012;Choi et al, 2019;Goncalo & Duguid, 2012;Goncalo & Staw, 2006;Lee & Choi, 2022;Wang et al, 2011;Ye & Robert, 2017). The participants were divided into different conditions (e.g., individualistic and collectivistic value orientations) based on manipulations before an ideation task to measure differences among groups and demonstrate the influence of culture on creativity (Goncalo & Staw, 2006).…”
Section: Experimental Samples Procedures and Tasksmentioning
confidence: 99%
“…Finally, in three studies, the authors judged creativity-related content (e.g., by counting the number of ideas). The metrics of creativity evaluation were varied, and they included flexibility (Choi et al, 2019), fluency (Bechtoldt et al, 2012), novelty (Choi et al, 2019;Lee & Choi, 2022), productivity (Wang et al, 2011), originality (Bechtoldt et al, 2012) and creativity (Goncalo & Duguid, 2012;Lee & Choi, 2022) (see Figure 2). For each metric, the authors employed different assessment methods.…”
Section: Measures To Evaluate Creativitymentioning
confidence: 99%